2017
DOI: 10.1007/s00253-017-8460-9
|View full text |Cite
|
Sign up to set email alerts
|

TCDD administered on activated carbon eliminates bioavailability and subsequent shifts to a key murine gut commensal

Abstract: Activated carbon (AC) is an increasingly attractive remediation alternative for the sequestration of dioxins at contaminated sites globally. However, the potential for AC to reduce the bioavailability of dioxins in mammals and the residing gut microbiota has received less attention. This question was partially answered in a recent study examining 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-induced hallmark toxic responses in mice administered with TCDD sequestered by AC or freely available in corn oil by oral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…That the fraction of released DD was less than 20% even for 99.9% methanol clearly indicated the strong affinity between DD and GAC; once sorbed DD appears to be largely irreversiblysequestered within the pore structure of GAC. The resistance to desorption, even into methanol, is consistent with our prior observation that sequestration of 2,3,7,8-TCDD by AC eliminated its mammalian bioavailability (Boyd et al, 2017;Stedtfeld et al, 2017).…”
Section: Desorption Of Ddsupporting
confidence: 90%
“…That the fraction of released DD was less than 20% even for 99.9% methanol clearly indicated the strong affinity between DD and GAC; once sorbed DD appears to be largely irreversiblysequestered within the pore structure of GAC. The resistance to desorption, even into methanol, is consistent with our prior observation that sequestration of 2,3,7,8-TCDD by AC eliminated its mammalian bioavailability (Boyd et al, 2017;Stedtfeld et al, 2017).…”
Section: Desorption Of Ddsupporting
confidence: 90%
“…A similar shift in SFB abundance was also observed in mice with a traditional gut microbiome; however, it was unknown if this was due to the expansion of other bacterial populations or changes in nutrients caused by commensal fluctuations. In detail, previous studies described an increased ratio of Firmicutes to Bacteroidetes in response to TCDD ( Lefever et al, 2016 ; Stedtfeld et al, 2017a ), and higher levels of Proteobacteria ( Stedtfeld et al, 2017b ). The expansion in these predominantly flagella producing groups ( Lozupone et al, 2012 ) may in part influence the relative levels of Bacteroidetes and SFB.…”
Section: Discussionmentioning
confidence: 91%
“…Emerging studies also suggest that environmental toxicants such as TCDD ( Lefever et al, 2016 ; Stedtfeld et al, 2017b ) and other AhR ligands interact with gut commensals ( Hubbard et al, 2015 ; Zhang et al, 2015 ; Murray et al, 2016 ). Previous murine studies with a traditional gut microbiome found that TCDD induced structural shifts in key bacterial populations; with increasing abundance of SFB ( Bhaduri, 2015 ; Stedtfeld et al, 2017a ) and decreasing abundance of Bacteroidetes in response to TCDD ( Lefever et al, 2016 ). Known opposing T-cell host responses to SFB and exposure to TCDD suggest that expansion of SFB could potentially abrogate or lessen TCDD-induced toxicity and differentiation of regulatory T-cells ( Marshall et al, 2008 ; Ivanov et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on how AhR activation or exposure to TCDD can directly or indirectly cause changes in the gut microbiota, bile acids, and SCFA metabolism [ 34 , 35 ]. Previous studies have shown that TCDD, when given orally to mice, caused a shift in mouse gut commensals [ 36 , 37 ]. TCDD was even shown to play a role in influencing a shift favoring bacteria that expressed antimicrobial resistance genes (ARGs) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%